Ocean current circulation modeling in the Bengkalis Strait in the east spring - Fajar Fajar; Elizal Elizal; Yusni Ikhwan Siregar (Science, Technology, and Education Care, 2023)
The waters of the Bengkalis Strait are geographically very strategic, directly connected to the waters of the Malacca Strait and a strategic water transportation route. One of the complex phenomena that appears in the waters of the Bengkalis Strait is the phenomenon of current movement. This survey was conducted from June to August 2022. The survey location was in the Bengkalis Strait, Bengkalis Regency, Riau Province. The research aims to determine current patterns and sea level height during the highest tides and lowest low tides each month during the east season in the waters of the Bengkalis Strait. The method used is a Survey and a quantitative descriptive method. All data is processed using MIKE 21 software. First, Google Earth was used to create bathymetry data, and then the boundaries of the survey area were determined using MIKE 21. After obtaining the bathymetry, we continued with the flow model using MIKE 21 and then displayed the results. Obtained results: the highest tide occurred on 13/06/2022 at 13:00 WIB with an average current discharge of 0.14-0.16 m/s, and the lowest wave occurred on 13/06/2022 at 20.00 WIB with an average flow rate of 0.60-0.75 m/s